Inequalities in Times of Pandemic: The Situation of Households with Girls, Boys and Adolescents in Ecuador - Samaniego, Pablo (2021)
The pandemic arrives in Ecuador in a year in which GDP contraction was expected due to the erratic economic policy of the regime inaugurated in May 2017 and the medium-term impact of the drop in oil prices between 2014 and 2016. Likewise, The economic policy that was applied since 2019 after the signing of the Expanded Service Agreement with the IMF, led to a cut in public spending, which weakened the main services of the social protection system and generated a strong outbreak of social protest in October 2019 The pandemic comes at a time of disarticulation and of the public discredit raised by the national government, and of the narrowing of the governance space. This policy had immediate consequences, especially in Guayaquil where the pandemic produced about 6,000 deaths in the first months and an excess of mortality close to 1,000%. In the midst of this situation, the economic policy model determined by the IMF and expanded by pressure from business sectors was deepened, approving the wrongly called Humanitarian Law, which, in substance, contains measures to make the formal labor market more flexible. The weakness of the government to face the pandemic has meant that a disease of universal scope has differentiated effects, that is, that socioeconomic inequality is expressed both in the incidence of the disease and in the significant deterioration of living conditions.